Optimization of distribution routes in resolving traveling salesman problems using the tabu search algorithm (case study: CV. Bintang anugerah sukses pekanbaru) - Basriati, Sri; Safitri, Elfira; Anggraini, Resi (Universitas Islam Negeri Raden Intan Lampung, 2021)
CV. Bintang Anugerah Sukses is a company engaged in the distribution of product PT. Belfoods Indonesia. Distribution of frozen goods distributes to 12 customer agencies using one vehicle. The route distribution is determined based on the experience and subjective decisions of a salesman in charge of distributing goods. The problem will be solved using the Travelling Salesman Problem (TSP) approach, so the best route for distributing goods can be obtained that can minimum mileage and time. One of the methods applied to the traveling salesman problem is the Tabu Search algorithm. Tabu Search is one of the metaheuristic methods with the process of searching moving from one solution to the next. The algorithm uses a taboo list to store a set of solutions that have just been evaluated, the result will be adjusted first to the contents of the taboo list to see whether the solution already exists or not. If the solution already exists then the solution will not be evaluated. The calculation results obtained a minimum mileage of 53.6 km and a minimum of time 305 minutes or 5 hours 5 minutes.